Humanizing Patients with a Holistic Care Approach to Improve their Psycho-Social-Spiritual Conditions - Mumtahanah, Silma; Khisoli, Alfis Khoirul (Universitas Muhammadiyah Yogyakarta, 2023)
The purpose of this study is to describe the process of spiritual guidance by implementing Holistic Health Care services performed by Bina Rohani officers in improving the patient's psycho-social-spiritual health. This qualitative research applied a descriptive analysis approach. Data collection techniques in this study were carried out by observation, in-depth interviews, and document review. The results of this study show that Bina Rohani plays a role in improving the psycho-social-spiritual health of patients side by side with nursing assessments using Holistic Health Care services. This is evidenced by positive changes in patients who experience problems in the psycho-social-spiritual aspect so that patients can worship, pray and read verses, have a feeling of peace, accept illness, and be ready to return to society without feeling inferior. The process of implementing spiritual guidance with Holistic Health Care services is carried out by spiritual development officers based on established Standard Operating Procedures (SOP).